The role of lncRNAs in hepatocellular carcinoma: opportunities as novel targets for pharmacological intervention. (3rd March 2016) - Zou, Hai; Shao, Chu-Xiao; Zhou, Qin-Yun; Zhu, Gui-Qi; Shi, Ke-Qing; Braddock, Martin; Huang, Dong-Sheng; Zheng, Ming-Hua
ABSTRACT: Long non-coding RNA (lncRNA) is commonly defined as an RNA with a length of greater than 200 nucleotides, frequently up to 100 kb. Numerous studies have shown that dysregulation of lncRNAs may directly relate to a number of human diseases, particularly in oncology where lncRNAs appear to play an important role. LncRNAs may also play a potentially novel and critical role in the development and progression of hepatocellular carcinoma (HCC). This article discusses lncRNAs as a new possibility for diagnostic and therapeutic approaches for HCC. The authors introduce the relationship between some lncRNAs and HCC, including carcinogenesis, development, metastasis and prognosis. In addition, the authors suggest that the discovery of lncRNAs may encourage the discovery and development of new therapeutic modalities for HCC and that their regulation may be a promising potential treatment for HCC. Clinical studies are required to determine the therapeutic effect of regulating lncRNA in humans with HCC.